MSC-derived microvesicles inhibit the progression of arthritis in a murine model of preclinical rheumatoid arthritis - Shixiong, Wei; Cheng, Ruijuan; Lu, Chengyang; Zhang, Qiuping; Li, Su Jia; Liu, Zhi-Hui; Wu, QiuHong; Pan, Shu-Yue; Li, Qiubai; Zeng, Xiao-Feng; Liu, Yi (Frontiers in Immunology, 2026)
ObjectivePreclinical rheumatoid arthritis (Pre-RA) represents a critical stage before the clinical manifestation of RA, characterized by autoimmune dysregulation. Early intervention in this stage can prevent the progression to full-blown RA. This study aimed to develop a robust murine model of Pre-RA and measure the therapeutic potential of mesenchymal stem cell-derived microvesicles (MSC-MVs) as a novel strategy to prevent the onset and progression of autoimmune arthritis.MethodsLow-concentration collagen emulsion was administered subcutaneously at the tail base on days 0 and 21 to establish the preclinical collagen-induced arthritis (Pre-CIA) model. Disease progression was assessed over 45 days based on CIA scoring, body weight monitoring, CT images, histopathology, laboratory tests, and flow cytometry. Pre-CIA mice were treated with MSC-MVs. The pharmacokinetic characteristics of MSC-MVs were measured using in vivo fluorescence imaging, and therapeutic efficacy was evaluated through CIA scoring, joint inflammation analysis, complementary imaging, and immunological assays.ResultsWe established a mouse model of Pre-CIA characterized by mild arthritis using reduced doses of immunizing agents. Pre-CIA mice were less likely to experience arthritis (59.09%) than CIA mice (95.45%). In addition, Pre-CIA mice exhibited gradual increases in CIA scores and increased histological damage, consistent with Pre-RA. LPS injection accelerated the rapid progression from Pre-CIA to CIA. Micro-CT revealed mild trabecular bone loss and joint erosion in Pre-CIA mice compared to severe damage in CIA mice. Histological staining demonstrated intermediate cartilage and bone damage in Pre-CIA mice, with significant synovial hyperplasia and cartilage loss. The serum levels of pro-inflammatory markers (IL-1β, TNF-α, IL-6, and CRP P<0.05) and RA-specific autoantibodies (anti-CII, and anti-CCP P<0.05) were upregulated in Pre-CIA mice. Flow cytometry revealed immune imbalances in Pre-CIA mice, with a decreased abundance of Tregs and Th2 cells and an increased abundance of Th1, Th17, and Tfh cells. Treatment with MVs prevented the progression of arthritis in Pre-CIA mice, reduced inflammatory marker levels, stabilized bone and cartilage integrity, and restored immune balance.ConclusionsThe Pre-CIA model effectively reflects the key pathological and immunological features of Pre-RA, providing a robust platform for studying disease mechanisms and early therapeutic interventions. Treatment with MSC-MVs successfully showed reversal of pathological features, highlighting their potential as a novel therapeutic strategy for preventing the progression of Pre-RA to full-blown rheumatoid arthritis. These findings underscore the clinical significance of MSC-MVs in addressing unmet needs in the early management of RA.